FLUDARABINE-BASED LOW-INTENSITY CONDITIONING FOR FANCONI ANEMIA IS ASSOCIATED WITH GOOD OUTCOMES IN APLASTIC ANEMIA BUT NOT IN MDS - A SINGLE-CENTER EXPERIENCE - George, Biju; Chattopadhyay, Sohini; Lionel, Sharon; Selvarajan, Sushil; Devasia, Anup; Korula, Anu; Kulkarni, Uday; Aboobacker, Fouzia; Sindhuvi, Eunice; Lakshmi, Kavitha; et al. (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: Hematopoietic stem cell transplantation [HSCT] is the only curative option for Fanconi Anemia (FA) patients with hematological abnormalities. Materials and Methods: This is a retrospective analysis of patients with FA who underwent a matched-related donor HSCT. Results: Sixty patients underwent 65 transplants between 1999-2021 using a fludarabine-based low-intensity conditioning regimen. The median age at transplant was 11 years (range: 3-37). Aplastic anemia (AA) was the underlying diagnosis in 55 (84.6%) while 8 (12.4%) had myelodysplastic syndrome (MDS) and 2 (3%) had acute myeloid leukemia (AML). The conditioning regimen used was fludarabine with low-dose cyclophosphamide for aplastic anemia and Fludarabine with low-dose busulfan for MDS/AML. Graft versus host disease (GVHD)prophylaxis consisted of cyclosporine and methotrexate. Peripheral blood stem cells was the predominant graft source (86.2%). Engraftment occurred in all but 1 patient. The median time to neutrophil and platelet engraftment was 13 days (range: 9-29) & 13 days (range: 5-31), respectively. Day 28 chimerism analysis showed complete chimerism in 75.4 % and mixed chimerism in 18.5%. Secondary graft failure was encountered in 7.7%. Grade II–IV acute GVHD occurred in 29.2% while Grade III-IV acute GVHD occurred in 9.2%. Chronic GVHD was seen in 58.5% and was limited in most patients. The median follow-up is 55 months [range: 2-144] & the 5-year estimated overall survival (OS) is 80.2 ± 5.1%. Secondary malignancies were noted in 4 patients. The 5-year OS was significantly higher in patients undergoing HSCT for AA (86.6 + 4.7%) as compared to MDS/AML (45.7+16.6%) (p= 0.001). Conclusion: SCT using a fully matched donor provides good outcomes with low-intensity conditioning regimens in patients with FA who have an aplastic marrow.